Healthcare Facilities and Services: Correlates to the Clinical Nursing Care for Patients with Psycho-Behavioral Pathologies in Lanao Del Sur - Abdulbasit, Omira; Hassim, Anieraida H.; Gallego, Randy Ian (JPAIR Multidisciplinary Research, 2018)
Mental health, for some time has been a facet downplayed to be of lesser importance due to its very mystical nature causing it to be habitually ignored. Albeit the case, mental illness and its similar disturbances can become so significantly serious that it can encroach on and impair the day-to-day activities of its stricken victims. This study examined the extent of preliminary clinical care provided by nurses to clients with unique psychological needs. It used the descriptive-correlational design through a validated and reliability-tested instrument responded by 113 staff nurses from six hospitals around Lanao del Sur. It involved the statistical analysis of data using frequency, weighted mean, and Pearson correlation. In addition, a triangulation procedure was also employed to incorporate qualitative narrative comments of the respondents through follow-up informant interviews and journal writing. The survey revealed that hospitals in the study locale do not have personnel with qualified specializations to attend to the needs of clients with psycho-behavioral manifestations. Moreover, the institutions did not have adequate physical facilities and equipment to aid in the appropriate diagnosis and management of mental conditions. It also showed that the availability of mental healthcare services, facilities, and personnel were significantly correlated to the extent of preliminary clinical nursing care. Hence, it can be regarded that these factors have a strong bearing and influence on the quality and extent of clinical care received by patients.